2011
DOI: 10.1103/physrevlett.107.016105
|View full text |Cite
|
Sign up to set email alerts
|

V2O3(0001)Surface Termination: Phase Equilibrium

Abstract: Complementary but independent medium-energy and low-energy ion scattering studies of the (0001) surfaces of V 2 O 3 films grown on Pd(111), Au(111) and Cu 3 Au(100) reveal a reconstructed full O 3 -layer termination creating a VO 2 surface trilayer. This structure is fully consistent with previous calculations based on thermodynamic equilibrium at the surface during growth, but contrasts with previous suggestions that the surface termination comprises a complete monolayer of vanadyl (V=O) species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 30 publications
(25 reference statements)
2
40
4
Order By: Relevance
“…Finally, we may ask whether, for these materials, the surface structure predicted to be in thermodynamic equilibrium with the gas phase under the preparation conditions of temperature and oxygen partial pressure is actually observed. In particular, previous studies of the (0001) faces of α-Al 2 O 3 [2,3,4] and Cr 2 O 3 [5,6,7,8,9] have indicated that is largely the case [10], but that for V 2 O 3 it is not (e.g. [10,11,12,13,14,15]).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we may ask whether, for these materials, the surface structure predicted to be in thermodynamic equilibrium with the gas phase under the preparation conditions of temperature and oxygen partial pressure is actually observed. In particular, previous studies of the (0001) faces of α-Al 2 O 3 [2,3,4] and Cr 2 O 3 [5,6,7,8,9] have indicated that is largely the case [10], but that for V 2 O 3 it is not (e.g. [10,11,12,13,14,15]).…”
Section: Introductionmentioning
confidence: 99%
“…There is some fine structure especially in the feature around 1300 cm −1 which points towards a number of slightly different adsorption states, but there are no indications that the states are significantly different for CO 2 on the oxide which contains mainly 18 O and the one prepared with 16 O, which may be viewed as an indication that it is not carbonate which is formed on the surface since this would involve a bond of CO 2 to surface oxygen. Another observation that points into the same direction is that CO 2 does not react with the vanadyl terminated surface, for which only molecular adsorption is found (see Fig.…”
Section: (B)mentioning
confidence: 95%
“…Crossley and King [33] have treated the frequency shifts of molecular vibrations in isotopic mixtures for the case of 13 CO and 12 CO on Pt(111) theoretically and measured the molecular vibrational energies with IRAS, finding a downward shift of the 12 CO band in the isotopic mixture, similar to what we find for the V= 16 O vanadyl vibration. A point to note is that the intensities of the V= 16 O and V= 18 O vanadyl vibrations in the bottom spectra in Fig. 3 are not proportional to the concentrations of 16 O and 18 O in the oxide layer since there is an intensity transfer from the low energy band to the high energy band [33][34][35][36].…”
Section: (B)mentioning
confidence: 99%
See 2 more Smart Citations